Digital-enabled service marketing mix transformation: A case study of Starbucks in international markets - Trian Hermawan; Anggalia Wibasuri; Nitami Sugiyati; Aep Saefulah; Ahmad Rughby; Setiaji Bintang Pamungkas (Privietlab, 2026)
This study examines how digital media and technology transform Starbucks’ marketing mix in international markets. Using a qualitative single-case study and document analysis, this article draws on Starbucks’ annual report, investor releases, official corporate documents, and academic literature on digital marketing, digital transformation, customer experience, CRM, omnichannel retailing, and marketing analytics. The analysis applies the 7P marketing mix framework: product, price, place, promotion, people, process, and physical evidence. The findings show that Starbucks uses digital technologies not only for promotion but also as an integrated marketing infrastructure linking mobile applications, Starbucks Rewards, Starbucks Card, Mobile Order and Pay, digital payment, customer data, physical stores, and barista services. The findings indicate that Starbucks’ marketing mix has shifted from a product-and-location-based system into an experience-, data-, loyalty-, and omnichannel-based system. However, this transformation creates strategic tensions between digital efficiency and human touch, personalization and data privacy, global standardization and local adaptation, and omnichannel access and operational capacity. The article contributes to digital marketing and service marketing literature by extending the 7P framework into a digital-enabled service marketing mix model.